South Asian dairy smallholders: A scoping review of practices and zoonoses - Emily Schembri; Angus J D Campbell; Juan Pablo Villanueva-Cabezas (Asian Pacific Journal of Tropical Medicine, 2023)
Objective: To identify and discuss on-farm management practices linked to bacterial zoonosis risk in smallholder dairy farmers in South Asia. Methods: This scoping review was conducted as per the PRISMA-ScR guidelines. Five hundred and two publications were retrieved from five online databases using a comprehensive search strategy. Studies were selected if they discussed a farm management practice which impacted human health within a South Asian country. Results: Twenty-two studies were included. Seven management practices relevant to farmers, livestock and their shared environment were identified including raw milk consumption, farm hygiene management, personal protective equipment uses, animal vaccination, cleaning udders, hand washing and disposal of afterbirth materials. Preventive practices were found to be utilized at lower frequencies compared to risk increasing practices. Awareness of bacterial zoonoses is particularly low within the region. Conclusions: Based on the results of this review, it was determined that improving farmer awareness of bacterial zoonotic diseases may favor several of the presented leverage points within the South Asian smallholder dairy system. Relying on formal school education to improve this awareness may not solve this problem, instead, more focus on accessible and affordable zoonoses education and farming programs is required.